Tingkat Kepuasan Pelayanan Pelanggan di Laundry Menggunakan Customer Satisfaction Index - Rival Gumilar (Universitas Pamulang, 2020)
This study aims to determine the level of satisfaction at the laundry customers. Customer satisfaction is indeed a priority for consumers. This analysis aims to differentiate satisfaction between consumers and others and service performance for consumers towards laundry, especially for students. The method used to collect the data / sample was a questionnaire using a satisfied to dissatisfied scale and the analysis method used was the customer satisfaction index (CSI). The results of the calculations performed obtained a CSI value of 80.46%, a meaningful value that indicates the criteria for service satisfaction obtained from consumers.